The Synergistic Effects of Astragalus mongholicus and Salvia miltiorrhiza on Coronary Heart Disease Identified by Network Pharmacology and Experiment - Zhang Y; Wang J; Liu YM; Chen YY; Yang XC; Duan L (Dove Medical Press, 2021)
Yun Zhang,1 Jie Wang,2 Yong-Mei Liu,2 Yin-Ying Chen,3 Xiao-Chen Yang,4 Lian Duan2 1Department of Immunology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 2Department of Cardiology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 3Department of the Scientific Research Office, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 4Department of Cardiology & Health Care, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of ChinaCorrespondence: Jie WangDepartment of Cardiology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of ChinaTel +86 010-88001148Email wangjiedoctor2015@163.comBackground and Purpose: Two Chinese herbal medicines Huang Qi (HQ, Astragalus mongholicus) and Dan Shen (DS, Salvia miltiorrhiza) are often combined to treat coronary heart disease (CHD). The purpose of this study was to identify the underlying synergistic effects and mechanisms of HQ and DS against CHD.Methods: The active components and targets of HQ and DS, CHD-related genes, and the biological progression were analysed by network pharmacology. The myocardial infarction (MI) rat model was established by ligating the left anterior descending coronary artery. Cardiac function was detected by ultrasonic electrocardiography. The MI size, fibrosis, cardiac hypertrophy, lipid metabolism, blood viscosity, and coagulation indexes were analysed by histological staining or chemical methods, respectively.Results: A total of 170 shared and specific seed genes of HQ and DS against CHD were identified. The shared and specific biological processes of HQ and DS against CHD were obtained. The LVEF and LVFS values significantly increased, the myocardium infarct size and fibrosis significantly decreased, the values of lipid metabolism indexes and blood viscosity indexes significantly reduced in the HQ + DS treatment group vs HQ or DS single treatment (P < 0.05); the LVEDd, LVEDs, and the CSA values significantly reduced in HQ single and HQ + DS treatment groups vs MI group (P < 0.05); the coagulation index (APTT, PT, TT, and FIB) values decreased significantly in the DS single and HQ + DS treatment groups vs MI group (P < 0.05).Conclusion: In MI rats, HQ and DS exhibited synergistic effects on improving cardiac function, reducing MI size, fibrosis, regulating hyperlipidaemia, and maintaining circulatory system homeostasis; HQ had the specific advantage of alleviating cardiac remodelling; DS had the specific advantage of regulating hypercoagulability. This study revealed that HQ and DS not only exerted synergistic effects but also exhibited complementary effects on CHD.Keywords: coronary heart disease, Astragalus mongholicus, Salvia miltiorrhiza, synergistic effects, network pharmacology, myocardial infarction